SOIL COVERAGE PLANTS PRECEEDING MAIZE CULTURE SUBMITTED TO DOSES OF NITROGEN FERTILIZATION - Pellin, Douglas Martins Pereira; Souza, Fábio Régis; Wendland, Sadrac Borges; Bergamin, Anderson Cristian; Vitorino, Antonio Carlos Tadeu; Colla, João Augusto Araújo (REVISTA DE AGRICULTURA, 2019)
This work aimed at evaluating the phytomass production and the accumulation of N in different soil coverage plants, as well as the effect of N doses applied in coverage on the maize cultivated in succession. The soil in the study area was classified as Dystroferric Red Latossoil with clayey texture. The experimental design used was the random blocks in factorial scheme of 5x4, with five coverage plants (millet, signalgrass, Crotalaria juncea, velvet bean, and fallow) anticipating the maize culture and four doses of mineral N (0; 67; 134; and 201 kg ha-1), with three repetitions. The crotalaria was efficient in the production of accumulated-N, being able to be indicated as forerunner culture to maize. The decomposition rate of the coverages was more accelerated in the first 42 days after the drying, as well as the mineralization of N. The maize culture reacted in na increasing way to the application of mineral-N